2021
DOI: 10.3390/children8060445
|View full text |Cite
|
Sign up to set email alerts
|

Needs and Experiences of Children and Adolescents with Pediatric Multiple Sclerosis and Their Caregivers: A Systematic Review

Abstract: In the present study we conduct a systematic review to evaluate the needs and experience of people with pediatric multiple sclerosis (MS) and their caregivers. The literature search was conducted across 10 academic databases, adhering to PRISMA-P guidelines. Quality appraisal was conducted using the mixed method appraisal test for individual studies, and GRADE-CERQual to establish overall confidence of findings. Results were analyzed using a process of narrative synthesis. We identified 26 studies which includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Indeed, stimulating the patients to accept their emotional responses to health-related limitations, while preserving their social and relational resources, seems key to the preservation of an adequate QoL over time. In particular, a recent review highlighted that an aspect that may reduce emotional distress in children and adolescents with MS is encouraging their own involvement during the diagnosis and decision-making process, as well as the relevance of an increased educational support by means of both increased awareness and disease specific accommodations [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, stimulating the patients to accept their emotional responses to health-related limitations, while preserving their social and relational resources, seems key to the preservation of an adequate QoL over time. In particular, a recent review highlighted that an aspect that may reduce emotional distress in children and adolescents with MS is encouraging their own involvement during the diagnosis and decision-making process, as well as the relevance of an increased educational support by means of both increased awareness and disease specific accommodations [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…POMS can be considered an "orphan" disease to all intents and purposes. Several studies have shown that there are still many unmet needs reported by children and adolescents affected by POMS, resulting not only from the physical and psychological effects of the disease in this specific age group but also from a lower availability of diagnostic and therapeutic information compared to the adult population (39). A recent meta-analysis analyzed 26 studies, including over 2,000 patients with POMS highlighting a profound negative impact on domains such as school performance, sociability and physical performance (39).…”
Section: Unmet Needs: Fears and Confusions Of Pomsmentioning
confidence: 99%
“…Several studies have shown that there are still many unmet needs reported by children and adolescents affected by POMS, resulting not only from the physical and psychological effects of the disease in this specific age group but also from a lower availability of diagnostic and therapeutic information compared to the adult population (39). A recent meta-analysis analyzed 26 studies, including over 2,000 patients with POMS highlighting a profound negative impact on domains such as school performance, sociability and physical performance (39). Specifically, the lack of adequate knowledge of the disease has been reported as one of the main barriers experienced by patients with POMS in carrying out their daily activities, with important repercussions on the possibility of social integration.…”
Section: Unmet Needs: Fears and Confusions Of Pomsmentioning
confidence: 99%
“…Additionally, the psychological consequences of POMS include feelings of incompetence and lower self-confidence, and social and physical anxiety, particularly when it occurs at a young age ( Carroll et al, 2016 ; Payamani et al, 2016 ). As such, POMS has a pronounced negative effect on school-related activities ( Carroll et al, 2016 ; Ghai et al, 2021 ) and can lead to a decreased quality of life ( Storm van's Gravesande et al, 2019 ; Omranifard et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%